WANITA DALAM BELENGGU NERAKA (Kritik Hadith Misoginis) - Talib Husain, Rahmin (IAIN Kediri, 2017)
The view toward women as second class human after men has been happened a long time. This stigma is risen from culture side, not from religious side, since in Islam there is no difference between men and women positions. Each human are equal in their capacity as human being. However, in fact, some religious texts from al-Qur’an and Hadith that are textually, partially and tendentiously understood unfortunately become tools to demeaning women. This article discusses one hadith misoginis about women as the majority of hell inhabitant through takhrīj al-ḥadīth approach and based on contextual understanding. Keywords: takhrīj al-ḥadīth, misoginis, women, contextual.